Drug-coated balloon angioplasty for drug-eluting stent restenosis: Insight from randomized controlled trials. (December 2014) - Mamuti, Wahafu; Jiamali, Abulimiti; Rao, Fang; Zhang, Wei; Pei, Xiaoli; Ablimit, Alimjan; Kelimu, Wumaierjiang; Zhang, Feng
Abstract Background. The best treatment option for drug-eluting stent (DES) restenosis has not been established. We performed a meta-analysis to assess the clinical efficacy of drug-coated balloon (DCB) for the treatment of DES restenosis. Methods. Trials were identified through a literature search from January 2005 through April 2014. All randomized controlled trials were eligible for inclusion if they compared DCB with a control treatment (plain old balloon angioplasty [POBA] or DES) in patients with DES restenosis. Results. Five studies and a total of 864 patients were included in this analysis. Most end-points were significantly reduced for DCB compared with the control groups. For major adverse cardiac events, the relative risk (RR) was 0.49 (P = 0.012); for target lesion revascularization, it was 0.50 (P = 0.044); for recurrent restenosis, it was 0.41 (P = 0.002). There was a lower mortality for DCB (RR 0.29; P = 0.017). The incidence of myocardial infarction was numerically lower, but without statistical significance (RR 0.76; P = 0.55). The DCB effect was more pronounced when compared with POBA than when compared with DES. Conclusions. This meta-analysis showed that DCB was superior to POBA and comparable to DES for treatment of DES restenosis. The findings in this meta-analysis cannot be extrapolated to DCB in general, because all DCB used in trials included was a single brand of paclitaxel-coated balloon.